POWER GENERATION FROM “PRO” PROCESS USING FLAT SHEET TFC–ULP KOCH MEMBRANES - Al–Hemiri, Adil; O. Sharif, Adel; T. Manji, Saif (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
The production of power using the process of pressure–retarded osmosis (PRO) has been studied both experimentally and theoretically for simulated sea water vs. river water and deionized water under two cases: the first is for simulated real conditions of sea water and river water and second under low brine solution concentration to examine the full profile of the power- pressure. The influence of concentration polarization (CP) on water flux has been examined as well.